Common principles for optimization of the athletes' acclimatization to hot and humid climate - T. Abramova; A. Akopyan; M. Aranson; L. Safonov; E. Kerimova (National Electronic Information Consortium (NEICON), 2020)
Objective: to develop an adaptation control technology to the hot climate for elite athletes. Materials and methods: data analysis, summarizing the experience of adaptation and acclimatization measures in preparation of national teams of Russia for the major international competitions; development and testing of integrated technologies for acceleration and optimization of the athletes' body state in the light of specific features of the sport in a hot and humid climate. Results: materials about preparation of teams of the USSR and Russia for the largest international competition in hot and humid climates were analyzed. ^e plan of implementation of an integrated management technology for adaptation of athletes was developed at the stage of immediate preparation for major competitions and included activities in three areas: organizational, scientific-methodical and educational. Methodological recommendations were developed including monitoring of the athletes' status and prevention of disorders of the major organs and systems. Conclusions: an acclimatization training camp should be advantageously carried out in an intermediate geographic area, similar in time zone, climatic and geographic characteristics of the competition place. The sport team should be moved to the competition place within two or three days before the championship's beginning. It is important to monitor hydration status, electrolyte balance and levels of key hormones in the process of adaptation.